Implementing the four levels a practical guide for effective evaluation of training programs - Kirkpatrick, Donald L. (San Francisco Berrett-Koehler Publishers, 2007)
The authors draw on their decades of collective expertise to offer time-tested advice for putting their training effectiveness model into practice. This new, concise, hands-on guide is designed as a companion volume to Donald Kirkpatricks bestselling "Evaluating Training Programs."
Includes bibliographical references (p. 135-136) and index.
Keywords: Employees--Training of--Evaluation.